Student to midwife transition: Newly qualified midwives' experiences in Limpopo province - Khathutshelo G. Simane-Netshisaulu (AOSIS, 2022)
Background: Regardless of educational pathway, the transition from student to the registered midwife is a topic of increasing interest within the profession as this is likely to have implications for retention and attrition. Newly qualified midwives have reported that the reality of putting knowledge into practice in the midwifery field is often challenging and stressful. Aim: To explore and describe the experiences of newly qualified midwives with regard to the provision of midwifery services during transition from students to qualified midwives, in the Limpopo province, South Africa. Setting: The study was conducted in the maternity units of each of the five selected public hospitals in the Limpopo province. Methods: The researcher employed a qualitative approach with explorative and descriptive design. The population comprised all midwifery graduates working in the Limpopo province and have undergone a comprehensive nursing programme regulated by R425 of 19 February 1985, as amended. Five newly qualified midwifery graduates were sampled from each of the five selected hospital, using a non-probability purposive sampling method, resulting in a sample size of 25 participants. Data collection was carried out through unstructured individual interviews and was conducted until participants were no longer bringing new information. Results: Graduates reported excessive workload, which resulted in physical exhaustion. Challenges related to the roles and responsibilities of a new position as a qualified midwife were expressed. Negative collegial relationship displayed by experienced qualified midwives, negatively affected graduates' midwifery performance. Conclusion: Effective, transition from student to qualified midwife is a stressful and exhausting process because of unfavourable working conditions in the labour ward, administrative roles as well as negative collegial relationship and disrespect displayed by experienced midwives. Contribution: Strategies to effectively support newly qualified midwives may be developed, which may consequently help in improving newly qualified midwives' performance.